STRATEGI EFEKTIF FUNDRAISING PADA LEMBAGA PENDIDIKAN ISLAM SWASTA - Hidayah, Khairu Ramadani Nurul; Bariroh, Umi; Fahrurrozi, Fahrurrozi (Jurnal Manajemen Pendidikan, 2025)
In developing an educational institution, cost factors and adequate educational staff must help each other to make the educational institution one of the best institutions for students. MI Miftahul Akhlaqiyah is one of the private Islamic educational institutions in Semarang that implements fundraising by paying attention to the surrounding community. This research aims to explain in more detail the selection of effective strategies to improve the quality of Islamic educational institutions, especially for private educational institutions, which until now have had to be smart in managing finances. The research method used is using a qualitative research type and approach, namely the researcher observes phenomena that occur directly in the field with various research subjects and is expressed in descriptive form based on natural methods. The results of the research show that MI Miftahul Akhlaqiyah uses various methods to raise funds. This fundraising is carried out starting from the involvement of students' parents or guardians, namely payment of tuition fees, registration payments, there is also fundraising from outside the madrasah. Not only that, Miftahul Akhlaqiyah also collaborates with UIN Walisongo in order to develop a library. Meanwhile, distribution comes from the foundation, then distribution of funds to expenditure of funds.